2014
DOI: 10.1021/la404344y
|View full text |Cite
|
Sign up to set email alerts
|

Electrowetting-Induced Droplet Detachment from Hydrophobic Surfaces

Abstract: Detachment of droplets from solid surfaces is a basic and crucial process in practical applications such as heat transfer and digital microfluidics. In this study, electrowetting actuations with square pulse signals are employed to detach droplets from a hydrophobic surface. The threshold voltage for droplet detachment is obtained both experimentally and theoretically to find that it is almost constant for various droplet volumes ranging from 0.4 to 10 μL. It is also found that droplets can be detached more ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
116
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(128 citation statements)
references
References 33 publications
(54 reference statements)
10
116
2
Order By: Relevance
“…The same physical mechanism has been applied in single-droplet, non-coalescence based, capillary-to-inertial energy conversion by melting-initiated 9,10 and electrowetting-actuated a) Author to whom correspondence should be addressed. Electronic mail: bush@math.mit.edu drop ejection, [11][12][13][14] for uses in micro-fabrication, droplet transfer across surfaces, and controlled dewetting of superhydrophobic surfaces. 15 However, these studies are primarily experimental, and the field is lacking a detailed physical model capable of predicting jumping behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The same physical mechanism has been applied in single-droplet, non-coalescence based, capillary-to-inertial energy conversion by melting-initiated 9,10 and electrowetting-actuated a) Author to whom correspondence should be addressed. Electronic mail: bush@math.mit.edu drop ejection, [11][12][13][14] for uses in micro-fabrication, droplet transfer across surfaces, and controlled dewetting of superhydrophobic surfaces. 15 However, these studies are primarily experimental, and the field is lacking a detailed physical model capable of predicting jumping behavior.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive approach for addressing these problems is to employ multiphase systems to isolate samples. Earlier studies have extensively demonstrated this on demand volume droplet generation, mixing, fusion, and concentration . The droplets or plugs can serve as discrete compartments enabling sample isolation and encapsulation for high‐throughput screening and as microchambers for individual cell lysis with limited dilution and cross‐contamination .…”
Section: Introductionmentioning
confidence: 99%
“…Agresti et al 19 was able to dielectrophoretically sort droplets according to fluorinated enzyme variants on the surfaces of yeast cells by presetting a fluorescence intensity threshold. Recent studies have also characterized droplet deformation due to the presence of a transverse alternating electric field 20 , and direct current (DC) electrowetting [21][22][23] . In a prior work (Wehking et al 24 ), we conducted a proofof-concept two-dimensional numerical simulation of electrically induced droplet deformation following the leaky dielectric model.…”
Section: Introductionmentioning
confidence: 99%